Melawan Stereotip pada Generasi Z dalam Pemberitaan Project Multatuli Serial #UnderprivilegedGenZ - Nuriyah Hanik Fatikhah; Asti Kurniawati; Mibtadin Anis Ahmad (Universitas Gadjah Mada, 2025)
Perceptions of Generation Z are often framed negatively, portraying them as lazy, spoiled, disloyal, and overly dependent on technology. These perspectives are generally produced by older generations and reinforced by state institutions and mainstream media. Within youth studies, such labeling is understood as a social construction emerging from intergenerational power relations that overlook the diversity of young people’s experiences shaped by social class, gender, and access to resources. This study analyzes Project Multatuli’s efforts to construct a counter-discourse through the #UnderprivilegedGenZ series. It employs Antonio Gramsci’s theory of counter-hegemony, Norman Fairclough’s critical discourse analysis to examine textual, discursive, and social practices, and a youth studies perspective to contextualize the construction of generational narratives. The findings show that Project Multatuli represents lower-class Generation Z individuals as subjects living within structural inequalities while maintaining agency. This narrative challenges the dominant, homogenizing, and moralistic portrayals in mainstream media and shifts public debate from individualized stereotypes toward an analysis of the social injustices shaping young people’s lives.